ANALYSIS OF WAITING PERIOD FOR MEN AFTER DIVORCE PERSPECTIVE OF JAMALUDDIN AṬIYAH'S MAQAṢID AS-SHARIA THEORY - Hasanuddin Hasanuddin; Muhammad Syukri Albani Nasution; Imam Yazid (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2021)
The Director General of Islamic Religious Institutional Development again issued Circular Number P-005 / DJ. III/Hk.00.7/10/2021 concerning marriage during the iddah period, according to the provisions of the circular "an ex-husband man can marry another woman when the iddah period of his ex-wife has ended". This article attempts to further analyze the waiting period for men due to talak raj'i divorce using Jamaluddin Aṭiyah's theory of maqashid as-sharia. This research is normative legal research. In the perspective of Maqashid As-Sharia proposed by Jamaluddin Aṭiyah, the regulation of waiting periods for men after divorce not only reflects aspects of Islamic law governing divorce, but also serves as a means to achieve broader goals in the lives of individuals, families, communities, and humanity by Islamic values. With this approach, the regulation has a profound impact on various aspects of life-related to divorce.Dirjen Pembinaan Kelembagaan Agama Islam kembali mengeluarkan surat Edaran Nomor P-005/DJ.III/Hk.00.7/10/2021 tentang pernikahan dalam masa iddah, menurut ketentuan edaran tersebut “laki-laki bekas suami dapat melakukan pernikahan dengan perempuan lain apabila telah selesai masa iddah bekas isterinya”. Artikel ini mencoba menganalisis lebih jauh terkait masa tunggu bagi laki-laki akibat perceraian talak raj’i dengan menggunakan teori maqashid as-syariah Jamaluddin Aṭiyah. Penelitian ini merupakan penelitian hukum normatif. Hasil penelitian ini menunjukan bahwa Dalam perspektif Maqashid As-Syariah yang dikemukakan oleh Jamaluddin Aṭiyah, regulasi masa tunggu bagi laki-laki setelah bercerai tidak hanya mencerminkan aspek hukum Islam yang mengatur peristiwa perceraian, tetapi juga berfungsi sebagai sarana untuk mencapai tujuan-tujuan yang lebih luas dalam kehidupan individu, keluarga, masyarakat, dan kemanusiaan sesuai dengan nilai-nilai Islam. Dengan pendekatan ini, regulasi tersebut memiliki dampak yang mendalam pada berbagai aspek kehidupan yang berkaitan dengan perceraian